Shift in phenotypic characteristics of enterotoxigenic Escherichia coli (ETEC) isolated from diarrheal patients in Bangladesh. - Yasmin Ara Begum; Nabilah Ibnat Baby; Abu S G Faruque; Nusrat Jahan; Alejandro Cravioto; Ann-Mari Svennerholm; Firdausi Qadri (Public Library of Science (PLoS), 2014)
Enterotoxigenic Escherichia coli (ETEC) is one of the most common causes of bacterial diarrhea. Over the last decade, from 1996 to 2012, changes in the virulence antigen properties of ETEC such as heat labile (LT) and heat stable (ST) toxins, colonization factors (CFs), and 'O'-serogroups have been observed. The aim of this prospective study was to compare changes in antigenic profiles of ETEC strains isolated from a 2% surveillance system at the icddr,b hospital in Dhaka, Bangladesh between 2007-2012 and an earlier time period of 1996-1998 conducted at the same surveillance site.In the surveillance system every 50th patient attending the hospital was screened for major enteric pathogens including ETEC, Vibrio cholerae, Shigella spp. and Salmonella spp. from January 2007 to December 2012.Of the 15,152 diarrheal specimens tested between 2007-2012, the overall rate of ETEC isolation was 11%; of these, 43% were LT/ST, 27% LT and 30% ST positive. Isolation rate of ST-ETEC (p<0.009) and LT/ST ETEC (p<0.011) during 2007-2012 period differed significantly compared to those seen between 1996-1998. In comparison to the 1996-1998 period, difference in CF profile of ETEC isolates during 2007-2012 was observed particularly for strains expressing CS7 (12.4%), CS14 (9.5%) and CS17 (10.0%). The predominant CF types were CS5+CS6, CFA/I, CS7, CS17, CS1+CS3, CS6 and CS14. The most common serogroups among the CF positive ETEC isolates were O115, O114, O6, O25 and O8. A strong association was found between CFs and 'O' serogroups i.e. between CS5+CS6 and (O115 and O126); CS7 and (O114), CFA/I and (O78 and O126), CS17 and (O8 and O167) and CS1/CS2+CS3 and (O6).The analyses show a shift in prevalence of antigenic types of ETEC over the study period; the information is important in designing effective ETEC vaccines with broad protective coverage.